Data Management Plan DSW Knowledge Models, Results of project 'Data Management Plans: Support Package for Norwegian Higher Education Libraries' - Ostrop, Jenny; Juhasz, Ida Benedicte; Bösl, Korbinian; Kvale, Live; Longva, Leif; Jahren, Lisbeth; Høier, Svein; Heggland, Ingrid (Zenodo, 2024)
Background information Adaption of two Data Management Plan (DMP) Knowledge Models and one export template developed in the project Data Management Plans: Support package for Norwegian higher education libraries (2023-2024), a collaboration between the University of Bergen, The Norwegian University of Science and Technology, the University of Oslo, UiT The Arctic University of Norway, PhD-On-Track and ELIXIR Norway. The Knowledge Models are to be used with the Open Source DMP tool Data Stewardship Wizard . Accompanying information resources to the Knowledge Models are available under: https://plan.research-data.no. Description Norwegian DSW Knowledge Model ID: elixir.no:dsw-km-no-localization:1.0.0 Version: 1.0.0 Metamodel: 16 Domain-agnostic Knowledge Model developed as deliverable in the project Data Management Plans: Support package for Norwegian higher education libraries (2023-2024, supported by the National Library of Norway). Adapted from the ELIXIR Norway Life Science DSW Knowledge Model originated from mindmap made by Rob Hooft. Parts of the considerations under 'List software/computational models/simulations that you will generate' are re-used from the Elixir Software Management Plan CC-BY 4.0 Question-specific guidance links to: https://plan.research-data.no/pages/support_00_start_writing Project phases: Initial, Midway, Complete Question tags can be combined in a modular way: Minimum: Questionnaire for less complex projects without personal/sensitive data, external partners, or external funding RCN/ Science Europe: Comprehensive questionnaire according to the RCN/ Science Europe recommendations (if combined with ELSI) ELSI: Additional questions for projects with ethical, legal, societal implications HPC: Additional questions for computationally demanding projects Additional question tags that can be used to customize project templates: umbrella DMP: Selection of questions for umbrella DMPs cross institutional project: Questions with relevance for projects involving external partners maDMP: Questions ...